Single Phase Full Bridge Inverter Control as Reactive Power Compensator - Anang Budhi Nugroho; Eka Firmansyah; Suharyanto Suharyanto (IJITEE (International Journal of Information Technology and Electrical Engineering), 2018)
The drop of local load voltage on the distribution system is an indicator that the system experiences reactive power shortage. It can be overcome by an inverter controlled to compensate reactive power. The benefit of the inverter is that it is easily configured with a variety of functions. This paper presents the control configuration of inverter as reactive power compensators. The method used is a current control system of the proportional integrator (PI) – dq based transformation. This method generates reactive power by regulating the current domain (Id, ref = 0), while the current domain (Iq,ref) is set according to the need. Phase locked loop (PLL) is added so that the inverter can be synchronized well with the grid. According to the analysis of the PI current control, the local load voltage is stable at 219.88 Vrms and the reactive power generated by the inverter is 298 VAR with steady state error 0.11% of the reference power without oscillation.